The timing and incidence of exploratory drilling on offshore wildcat tracts - Hendricks, Kenneth; Porter, Robert H. (American Economic Review, 1996)
This paper documents exploratory drilling activity on offshore wildcat oil and gas leases in the Gulf of Mexico sold between 1954 and 1980. The authors calculate the empirical drilling hazard function for cohorts in specific areas. For each year of the lease, they study the determinants of the decision whether to begin exploratory drilling and their relationship to the outcome of any drilling activity. Their results indicate that equilibrium predictions of plausible noncooperative models are reasonably accurate and more descriptive than those of cooperative models of drilling timing. The authors discuss why noncooperative behavior may occur and the potential gains from coordination. Copyright 1996 by American Economic Association.